The Role of Motivation to Productivity Performance Teacher MI Al Iman Daarussalaam in Learning the New Era Normal - Nur Rohmad; Minzani Aufa; Farida Uswatun Khasanah; Rovi Nursari; Evi Nur Cahyani; Siti Nur Ummah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The purpose of the study was to recognize the motivation and productivity of the performance of the Islamic Elementary School Teacher (MI) Al Imanan Daarussalaam in learning in the Normal era. The main information and data sources obtained from the research subjects namely the population of 10 people, consisting of 1 Madrasah Head and 9 Teachers. Data collection techniques are observation, interviews, documentation, and questionnaires. Data analysis techniques use descriptive. Based on the research obtained data that: a) MI teachers have carried out online and offline learning in accordance with the capabilities of each teacher, b) the need for motivation from the head of the madrasa so that the teacher's awareness in increasing its performance can increase towards positively.